1996
DOI: 10.1074/jbc.271.28.16466
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Cross-reactivity within the Protease-activated Receptor Family

Abstract: Recently, a second member of the protease-activated receptor (PAR) family, named PAR-2, has been identified. Similar to the thrombin receptor, PAR-2 appears to be activated by proteolytic-mediated exposure of a "tethered ligand" sequence and can also be activated by the corresponding synthetic peptides. Similarities in the amino acid sequence of the receptors' tethered ligand sequences suggest that their respective agonist peptides might not be absolutely specific for their particular receptors. To test this, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
192
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(201 citation statements)
references
References 30 publications
7
192
2
Order By: Relevance
“…This suggests that colonic cancer cells may have an exquisite sensitivity to trypsin. However, the effects of trypsin on colonic cancer cell proliferation are clearly mediated by PAR-2 since we showed that the specific agonist of PAR-2, AP2 (Blackhart et al, 1996;Hollenberg et al, 1997) also promoted cell proliferation, mimicking the trypsin effect. In contrast the reverse peptide with the reverse AP2 peptide sequence was devoid of any mitogenic effect.…”
Section: Discussionmentioning
confidence: 74%
“…This suggests that colonic cancer cells may have an exquisite sensitivity to trypsin. However, the effects of trypsin on colonic cancer cell proliferation are clearly mediated by PAR-2 since we showed that the specific agonist of PAR-2, AP2 (Blackhart et al, 1996;Hollenberg et al, 1997) also promoted cell proliferation, mimicking the trypsin effect. In contrast the reverse peptide with the reverse AP2 peptide sequence was devoid of any mitogenic effect.…”
Section: Discussionmentioning
confidence: 74%
“…PAR-2 seems to be activated physiologically mainly by trypsin (Nystedt et al, 1995). PAR-1 and PAR-4 are also activated by trypsin, although these two PARs are considered predominantly as thrombin receptors (Vouret-Craviari et al, 1995;Blackhart et al, 1996;Xu et al, 1998). To date no attempts have been undertaken to explore whether the various isoforms of trypsin differ in their ability to activate PARs.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies of PAR1 used agonist peptides that were later shown to activate PAR2 (Blackhart et al, 1996;Hollenberg et al, 1997). Over time, relatively speciÂźc agonist peptides have been described for PAR1, PAR2, and PAR4 (Table 1) (Blackhart et al, 1996;Xu et al, 1998;Faruqi et al, 2000;Hollenberg et al, 1997;Brass et al, 1992). In some cells, one can now tease out contributions from individual PAR subtypes, and conÂźrm distribution data with functional correlates of receptor expression.…”
Section: Which Receptor(s) Contribute To Thrombin Responses In Any Pamentioning
confidence: 99%
“…Granzyme A (Suidan et al, 1994(Suidan et al, , 1996. c Structure/activity relationships have been explored in some detail for short peptides (up to 14 amino acids) that activate PAR1 and PAR2 Scarborough et al, 1992;Al-Ani et al, 1999;Hollenberg et al, 1992Hollenberg et al, , 1997Blackhart et al, 1996;Chao et al, 1992;Natarajan et al, 1995;Kawabata et al, 1999), and more recently for PAR4 (Kahn et al, 1998b(Kahn et al, , 1999Hollenberg et al, 1999;Faruqi et al, 2000). To date, no peptide activators of PAR3 have been described (Hollenberg, 1999).…”
Section: Which Receptor(s) Contribute To Thrombin Responses In Any Pamentioning
confidence: 99%